2011
DOI: 10.1016/j.jvs.2011.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative versus surgical management of small (less than 3 cm), asymptomatic popliteal artery aneurysms

Abstract: Popliteal artery aneurysms represent a common pathology that vascular surgeons are often confronted with. However, several issues remain incompletely understood, including indications for intervention and optimal methods of treatment. In the following article, our discussants debate the appropriate management of small popliteal artery aneurysms. Further complicating this discussion is the unclear relationship between popliteal artery aneurysm diameter and subsequent complications. Whereas with abdominal aortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…Some advocate that all PAAs should be repaired, regardless of size, because of the high complication and amputation rates after ALI. 20 Even when PAAs are initially asymptomatic, patients will develop symptoms at a mean rate of 14% per year (range, 5%e24%), 21 and one third will develop ALI within five years. 22 In patients selected for anticoagulation and/or routine surveillance due to small aneurysm size (2e3 cm) or coexisting cardiovascular or malignant disease, 33%e45% eventually need surgical management anyway.…”
Section: Discussionmentioning
confidence: 99%
“…Some advocate that all PAAs should be repaired, regardless of size, because of the high complication and amputation rates after ALI. 20 Even when PAAs are initially asymptomatic, patients will develop symptoms at a mean rate of 14% per year (range, 5%e24%), 21 and one third will develop ALI within five years. 22 In patients selected for anticoagulation and/or routine surveillance due to small aneurysm size (2e3 cm) or coexisting cardiovascular or malignant disease, 33%e45% eventually need surgical management anyway.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis of asymptomatic PAA is helpful to avoid emergency repair and provide the best chance for long-term bypass or stent graft patency and limb salvage. 13 Indications for PAA repair include (1) size >2 cm in diameter, particularly if significant mural thrombus is present; (2) local compression or lower extremity ischemia symptoms (claudication, rest pain, or tissue loss); (3) rapid growth; (4) acute thrombosis or distal embolization; and (5) rupture. 6,14 Some authors have suggested aggressive repair of PAAs with a diameter of <2 cm if thrombus is present 15 because the amputation rate for acute thrombosis of a PAA is as high as 30%.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomographic angiography (CTA), magnetic resonance angiography, and/or invasive arteriography are necessary to plan an endovascular treatment. 16 In all cases PAA diagnosis was achieved with DUS. In group A, patients underwent additionally to CTA in order to assess PAA anatomical findings and the feasibility of endovascular treatment.…”
Section: Discussionmentioning
confidence: 99%